Mitochondrial variation of wild populations of two brackish ricefish (Teleostei: Beloniformes) in Thailand - Ngamniyom, Arin; Duangjai, Wirongrong; Racharak, Phruet; Wongroj, Weerawich; Karnchaisri, Kriangkrai; Soe, Babi Kyi; Siriwattanarat, Ruthairat (Agriculture and Natural Resources, 2022)
Importance of the work: Both the Javanese ricefish (Oryzias javanicus) that is distributed in brackish water and the Indian ricefish (O. dancena) that inhabits brackish or freshwater are utilized as aquatic animal models in biological experiments. However, the population genetics of these two species in Thailand are unknown. Objectives: To report on the genetic diversity of Javanese and Indian ricefish in Thailand. Materials & Methods: The genetic diversity of Javanese and Indian ricefish were analyzed based on cytochrome c oxidase subunit 1 (COI, 750 bp in length). Results: The Javanese ricefish populations were separated into two groups. Group 1 was composed of Javanese ricefish collected mainly from the Andaman Sea. Group 2 consisted of the fish populations in the Gulf of Thailand. Evidence of cryptic species was found in the Javanese ricefish group 2 (considered as O. cf. javanicus). The Indian ricefish were also distinguished into groups 1 and 2, where group 1 consisted mainly of Indian ricefish living in the Andaman Sea, while those inhabiting the Gulf of Thailand were phylogenetically placed in group 2. The demographics indicated that the population size was stable for both species, with genetic diversity also discussed. Main finding: The genetic diversity among populations of brackish ricefish in Thailand may be is associated with the biogeographical regions of the Gulf of Thailand and the Andaman Sea.